Stimulation of RAC1/PAK1 signalling upregulates DNA damage repair genes via the BCL6/STAT5-switch - Barros, Patrícia (2018)
Colorectal cancer is one of the most prevalent types of cancer worldwide. The GTPase RAC1 and its effector PAK1 have been found overexpressed or hyperactivated in colorectal cancers, particularly those with more aggressive and invasive features, leading to unfavourable clinical prognosis, often resulting from chemoresistance.